Comparison of optomotor and optokinetic reflexes in mice - Kretschmer, Friedrich; Tariq, Momina; Chatila, Walid; Wu, Beverly; Badea, Tudor Constantin (Journal of neurophysiology, 2017)
During animal locomotion or position adjustments, the visual system uses image stabilization reflexes to compensate for global shifts in the visual scene. These reflexes elicit compensatory head movements (optomotor response, OMR) in unrestrained animals or compensatory eye movements (optokinetic response, OKR) in head-fixed or unrestrained animals exposed to globally rotating striped patterns. In mice, OMR are relatively easy to observe and find broad use in the rapid evaluation of visual function. OKR determinations are more involved experimentally but yield more stereotypical, easily quantifiable results. The relative contributions of head and eye movements to image stabilization in mice have not been investigated. We are using newly developed software and apparatus to accurately quantitate mouse head movements during OMR, quantitate eye movements during OKR, and determine eye movements in freely behaving mice. We provide the first direct comparison of OMR and OKR gains (head or eye velocity/stimulus velocity) and find that the two reflexes have comparable dependencies on stimulus luminance, contrast, spatial frequency, and velocity. OMR and OKR are similarly affected in genetically modified mice with defects in retinal ganglion cells (RGC) compared with wild-type, suggesting they are driven by the same sensory input (RGC type). OKR eye movements have much higher gains than the OMR head movements, but neither can fully compensate global visual shifts. However, combined eye and head movements can be detected in unrestrained mice performing OMR, suggesting they can cooperate to achieve image stabilization, as previously described for other species. NEW & NOTEWORTHY We provide the first quantitation of head gain during optomotor response in mice and show that optomotor and optokinetic responses have similar psychometric curves. Head gains are far smaller than eye gains. Unrestrained mice combine head and eye movements to respond to visual stimuli, and both monocular and binocular fields are used during optokinetic responses. Mouse OMR and OKR movements are heterogeneous under optimal and suboptimal stimulation and are affected in mice lacking ON direction-selective retinal ganglion cells.